脂肪相关淋巴簇作为多种组织的移植、组织再生、器官发生和功能的位点 (2024)
本公开涉及脂肪相关淋巴簇("FALC"或"乳斑")中细胞的植入或增殖，其可以用于生成功能性异位组织。本公开还提供了用于通过激活淋巴毒素β受体(LTβR)和/或NF-κB诱导激酶(NIK)信号转导途径在FALC中移植细胞和使细胞增殖的方法和组合物。本公开还提供了在FALC(乳斑)中建立异位肝脏组织并将这类异位肝脏组织用于获得治疗益处的方法和组合物，并且提供了在FALC中生成异位肾组织的方法和组合物，其可以用于在对象中获得治疗益处。 The present disclosure relates to the engraftment and proliferation of cells in fat-associated lymphoid clusters ("FALCs" or "milky spots"), which may be used to generate functional ectopic tissue. The present disclosure further provides methods and compositions for grafting and proliferating cells, in FALCs by activating the lymphotoxin beta receptor (LTβR) and/or NF-κB-inducing kinase (NIK) signaling pathway. The present disclosure also provides for methods and compositions to establish ectopic liver tissue in FALCs (milky spots) and to use such ectopic liver tissue for therapeutic benefit, and provides methods and compositions to generate ectopic kidney tissue in FALCs, which can be used in a subject for therapeutic benefit.